Bunjevci from Bačka – Language and Identity - Vuković, Petar (Poznańskie Studia Slawistyczne, 2015)
Bunjevci from the region of Bačka are a deeply divided community: some of them believe they are a separate ethnic group with a distinct language, while others claim they are a subgroup of Croats and speak a Croatian dialect. The paper explains historical roots of the group’s divided ethnic consciousness and explores its consequences on the construction of their contemporary identities. First, the formation of Bunjevci as a pre-modern ethnicity in Dalmatia is discussed. It is followed by an account of historical experiences of those of them who later migrated to the Danube region in Hungary. The paper is concluded by a comparison between the Bunjevci’s two models of language regulation and politics of memory.